2018
DOI: 10.1111/ijd.14356
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, risk factors, and outcomes of adult cutaneous non‐tuberculous mycobacterial infection over a 10‐year period in Singapore

Abstract: Background Unfamiliarity with the presentation, diagnostic process, and treatment of cutaneous non‐tuberculous mycobacterium (NTM) infection leads to poorer outcomes. We describe our experience with managing cutaneous NTM infection in a regional hospital in Singapore from 2005 to 2014. Methods Adult patients with cutaneous NTM infections were identified through positive skin tissue cultures in this retrospective case series. We excluded patients younger than 21 years of age, patients whose care was transferred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…of M. mageritense bacteremia followed by skin abscess, although skin and soft tissue infection is a common presentation of non-tuberculous mycobacterium infection (11).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…of M. mageritense bacteremia followed by skin abscess, although skin and soft tissue infection is a common presentation of non-tuberculous mycobacterium infection (11).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The present study identified 5 MTB and 55 NTM positive cutaneous infections by combining clinical spectrum and etiological examination. In general, the incidence of NTM infections has been on the rise ( Wentworth et al., 2013 ; Mei et al., 2019 ; Yeo et al., 2019 ) and the same was evidenced by the increased number of cutaneous mycobacterial infection cases detected from 2019 to 2021 in our hospital. In addition to the general increase of infections, improved diagnostic accuracy was responsible for the augmented incidence of cutaneous mycobacterial infections ( Wang and Pancholi, 2014 ).…”
Section: Discussionmentioning
confidence: 55%
“…Combined antibiotics treatment is often required, and surgical therapy may be needed optionally ( Philips et al, 2019 ). After reviewing several in vitro antimicrobial susceptibility research ( Forbes et al, 2018 ; Yeo et al, 2019 ; Da et al, 2020 ; Kumar et al, 2021 ; Das et al, 2022 ), we found that M. fortuitum strains were susceptible to many antibiotics. The isolates are susceptible to amikacin (intermediate to highly sensitive), ciprofloxacin (highly susceptible), doxycycline (intermediate susceptible), clofazimine, trimethoprim-sulfamethoxazole (TMP-SMX) and linezolid, resistance to all the antituberculosis agents, while different to macrolides (decreased sensitivity due to inducible susceptibility) and imipenem.…”
Section: Main Textmentioning
confidence: 93%